Transport modeling of the DIII-D high βp scenario and extrapolations to ITER steady-state operation. (3rd August 2017) - McClenaghan, J.; Garofalo, A.M.; Meneghini, O.; Smith, S.P.; Leuer, J.A.; Staebler, G.M.; Lao, L.L.; Park, J.M.; Ding, S.Y.; Gong, X.; Qian, J.
Abstract: Transport modeling of a proposed ITER steady-state scenario based on DIII-D high poloidal-beta ( β p ) discharges finds that ITB formation can occur with either sufficient rotation or a negative central shear q-profile. The high β p scenario is characterized by a large bootstrap current fraction (80%) which reduces the demands on the external current drive, and a large radius internal transport barrier which is associated with excellent normalized confinement. Modeling predictions of the electron transport in the high β p scenario improve as q 95 approaches levels similar to typical existing models of ITER steady-state and the ion transport is turbulence dominated. Typical temperature and density profiles from the non-inductive high β p scenario on DIII-D are scaled according to 0D modeling predictions of the requirements for achieving a Q = 5 steady-state fusion gain in ITER with 'day one' heating and current drive capabilities. Then, TGLF turbulence modeling is carried out under systematic variations of the toroidal rotation and the core q-profile. A high bootstrap fraction, high β p scenario is found to be near an ITB formation threshold, and either strong negative central magnetic shear or rotation in a high bootstrap fraction are found to successfully provide the turbulence suppression required to achieve Q = 5 .